Recombinant BCGs for tuberculosis and bladder cancer. Issue 50 (8th December 2021) - Singh, Alok K.; Srikrishna, Geetha; Bivalacqua, Trinity J.; Bishai, William R.
Abstract: Bacillus Calmette–Guérin (BCG) vaccine is an attenuated live strain of Mycobacterium bovis. It may be the most widely used vaccine in human history and is the only licensed human tuberculosis (TB) vaccine available. Despite its excellent safety history, a century of use in global vaccination programs, and its significant contribution to reducing TB mortality among children, the efficacy of BCG continues to be disputed due to its incomplete protection against pulmonary TB in adults. Still vaccines offer the best chance to contain the ongoing spread of multi-drug resistance TB and disease dissemination. The development of improved vaccines against TB therefore remains a high global priority. Interestingly, recent studies indicate that genetically modified BCG, or administration of existing BCG through alternate routes, or revaccination, offers improved protection, suggesting that BCG is well poised to make a comeback. Intravesical BCG is also the only approved microbial immunotherapy for any form of cancer, and is the first-line therapy for treatment-naïve non-muscle invasive bladder cancer (NMBIC), which represents a majority of the new bladder cancer cases diagnosed. However, almost a third of patients with NMIBC are either BCG unresponsive or have tumor recurrence, leading to a higher risk of disease progression. With very few advances in intravesical therapy over the past two decades for early-stage disease, and a limited pipeline of therapeutics in Phase 3 or late Phase 2 development, there is a major unmet need for improved intravesical therapies for NMIBC. Indeed, genetically modified candidate BCG vaccines engineered to express molecules that confer stronger protection against pulmonary TB or induce potent anti-tumor immunity in NMIBC have shown promise in both pre-clinical and clinical settings. This review discusses the development of second generation, genetically modified BCG candidates as TB vaccines and as anti-tumor adjuvant therapy for NMIBC.